Dealing with PET radiometabolites - Ghosh, Krishna Kanta (2020)
Positron emission tomography (PET) offers the study of biochemical, physiological, and pharmacological functions at a cellular and molecular level. The performance of a PET study mostly depends on the used radiotracer of interest. However, the development of a novel PET tracer is very difficult, as it is required to fulfill a lot of important criteria. PET radiotracers usually encounter different chemical modifications including redox reaction, hydrolysis, decarboxylation, and various conjugation processes within living organisms. Due to this biotransformation, different chemical entities are produced, and the amount of the parent radiotracer is declined. Consequently, the signal measured by the PET scanner indicates the entire amount of radioactivity deposited in the tissue; however, it does not offer any indication about the chemical disposition of the parent radiotracer itself. From a radiopharmaceutical perspective, it is necessary to quantify the parent radiotracer's fraction present in the tissue. Hence, the identification of radiometabolites of the radiotracers is vital for PET imaging. There are mainly two reasons for the chemical identification of PET radiometabolites: firstly, to determine the amount of parent radiotracers in plasma, and secondly, to rule out (if a radiometabolite enters the brain) or correct any radiometabolite accumulation in peripheral tissue. Besides, radiometabolite formations of the tracer might be of concern for the PET study, as the radiometabolic products may display considerably contrasting distribution patterns inside the body when compared with the radiotracer itself. Therefore, necessary information is needed about these biochemical transformations to understand the distribution of radioactivity throughout the body. Various published review articles on PET radiometabolites mainly focus on the sample preparation techniques and recently available technology to improve the radiometabolite analysis process. This article essentially summarizes the chemical and structural identity of the radiometabolites of various radiotracers including [11C]PBB3, [11C]flumazenil, [18F]FEPE2I, [11C]PBR28, [11C]MADAM, and (+)[18F]flubatine. Besides, the importance of radiometabolite analysis in PET imaging is also briefly summarized. Moreover, this review also highlights how a slight chemical modification could reduce the formation of radiometabolites, which could interfere with the results of PET imaging.